2021
DOI: 10.1002/essoar.10507192.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Freshwater input and vertical mixing in the Canada Basin's seasonal halocline: 1975 vs 2006-2012

Abstract: The seasonal halocline impacts the exchange of heat, energy, and nutrients between the surface and the deeper ocean, and it is changing in response to Arctic sea ice melt over the past several decades. Here, we assess seasonal halocline formation in 1975 and 2006-2012 by comparing daily, May to September, below-ice salinity profiles collected in the Canada Basin. We evaluate differences between the two time periods using a one-dimensional (1D) bulk model to quantify differences in freshwater input and vertical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
3
3
0
Order By: Relevance
“…There were four occupied AIDJEX ice camps between May 1975 and April 1976 and 30 ITPs, which were available for 2004-2012 at the time of the analysis. The data in this study are identical to those employed by Rosenblum et al (2021), who showed that June-September surface changes between the ITP and AIDJEX datasets are consistent with 30-year mixedlayer trends reported by Peralta-Ferriz and Woodgate (2015) using data mainly associated with low sea ice concentration in the same region. They used only quality-controlled data (level 3) in the ITP archive, screened profiles to select those that include samples shallower than 10 m depth (as in Jackson et al, 2010), and that were collected during the period May 1 -December 31, which is common to both datasets.…”
Section: Accepted Articlesupporting
confidence: 85%
“…There were four occupied AIDJEX ice camps between May 1975 and April 1976 and 30 ITPs, which were available for 2004-2012 at the time of the analysis. The data in this study are identical to those employed by Rosenblum et al (2021), who showed that June-September surface changes between the ITP and AIDJEX datasets are consistent with 30-year mixedlayer trends reported by Peralta-Ferriz and Woodgate (2015) using data mainly associated with low sea ice concentration in the same region. They used only quality-controlled data (level 3) in the ITP archive, screened profiles to select those that include samples shallower than 10 m depth (as in Jackson et al, 2010), and that were collected during the period May 1 -December 31, which is common to both datasets.…”
Section: Accepted Articlesupporting
confidence: 85%
“…The surface ocean also became more stably stratified, with a reduction in the mixed layer depth of 8 m and a reduction of the sea surface salinity of 2.3 psu, in agreement with Rosenblum, Stroeve, et al. (2021). A warming signal in the vertical temperature profile at a similar depth range as the winter Pacific Waters also starts to appear in the early 2000s (two bumps in Pacific Waters range, consistent with Toole et al., 2010); whether this is due to under‐sampling or warming is not clear.…”
Section: Resultssupporting
confidence: 87%
“…In addition, the observed transition to a shallower mixed layer from the 1970s to the 2010s is missing in the CESM1‐LE. From the 1970s (AIDJEX) to the early 2000s (ITP), there is a large freshening of the surface water for all months and a clear reduction of the May mixed layer depth (Figures 6a and 6c; see also Peralta‐Ferriz & Woodgate (2015); Rosenblum, Stroeve, et al., 2021). Yet, in the CESM1‐LE, there is only a small freshening of the surface water (Figures 6b and 6d) and the May mixed layer thickens instead (∼10 m over a 40‐year period in the mean, significant at ∼100%, Figure 7).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, model biases in upper ocean stratification and vertical mixing need to be reduced in order to accurately capture this increasingly important driver of Arctic sea ice variability. These biases could be reduced by increasing the vertical resolution of the upper ocean to properly resolve the shallow summer mixed layer (Rosenblum et al, 2021).…”
Section: Discussionmentioning
confidence: 99%